Chromatin domain alterations linked to 3D genome organization in a large cohort of schizophrenia and bipolar disorder brains - Girdhar, Kiran; Hoffman, Gabriel E.; Bendl, Jaroslav; Rahman, Samir; Dong, Pengfei; Liao, Will; Hauberg, Mads E.; Sloofman, Laura; Brown, Leanne; Devillers, Olivia; Kassim, Bibi S.; Wiseman, Jennifer R.; et al. (Nature neuroscience, 2022)
Chromosomal organization, scaling from the 147-base pair (bp) nucleosome to megabase-ranging domains encompassing multiple transcriptional units, including heritability loci for psychiatric traits, remains largely unexplored in the human brain. In this study, we constructed promoter- and enhancer-enriched nucleosomal histone modification landscapes for adult prefrontal cortex from H3-lysine 27 acetylation and H3-lysine 4 trimethylation profiles, generated from 388 controls and 351 individuals diagnosed with schizophrenia (SCZ) or bipolar disorder (BD) ( n = 739). We mapped thousands of cis -regulatory domains (CRDs), revealing fine-grained, 10 4 –10 6 -bp chromosomal organization, firmly integrated into Hi-C topologically associating domain stratification by open/repressive chromosomal environments and nuclear topography. Large clusters of hyper-acetylated CRDs were enriched for SCZ heritability, with prominent representation of regulatory sequences governing fetal development and glutamatergic neuron signaling. Therefore, SCZ and BD brains show coordinated dysregulation of risk-associated regulatory sequences assembled into kilobase- to megabase-scaling chromosomal domains. Girdhar et al. constructed chromosomal domains from prefrontal histone acetylation and methylation maps and discovered, in a large cohort of schizophrenia and bipolar brains, converging alignment by genetic risk, neuronal function and three-dimensional genomics.